Effectiveness of early oseltamivir treatment in children with pandemic 2009 A/H1N1 influenza in the Vilnius University Children Hospital - Usonis, Vytautas; Narkevičiūtė, Irena; Guntaitė, Vilija (Acta medica Lituanica, 2013)
Background. Oseltamivir is recommended for treatment of pandemic influenza in children. The therapy should be started as soon as possible, however, data on the effectiveness of such a treatment is rather limited. This study was accomplished in order to evaluate the effectiveness of oseltamivir depending on the time of the beginning of treatment. Materials and methods. Medical records of 72 children hospitalised to the Vilnius University Children’s Hospital (VUCH) because of laboratory confirmed pandemic influenza during November–December 2009 were analysed retrospectively. Duration of fever and frequency of complications in children treated with oseltamivir starting on days 1–2 and those who were started to treat ≥day 3 from the beginning of flu symptoms were compared to those who did not receive oseltamivir. Results. 40 patients were treated with oseltamivir: 20 children were commenced on treatment within 48 hours of their illness and the other 20 were started on oseltamivir on day 3 or later. 32 children were not treated with oseltamivir. Fever lasted 2.1 ± 0.8 days if the treatment with oseltamivir was started within 48 hours of illness and 4.1 ± 1.9 days if the treatment was started later (p